Lipid Peroxidation and Thymidine Phosphorylase expression in Prostate Carcinoma - Tandon, R; Rath, U S; Pande, D; Negi, R; Karki, K; Khanna, H D (Journal of stress physiology & biochemistry, 2012)
Aim: To understand the association between markers of oxidative stress and angiogenesis in relation to disease progression, clinical stage and cytological grade in patho-physiology of prostate carcinoma. Patients and Methods: Case control study comprised of 50 prostate carcinoma patients along with 20 age and sex-matched healthy subjects as controls. Levels of malondialdehyde were measured to study the oxidative stress status in the study subjects. Angiogenesis was evaluated by studying the activity of Thymidine Phosphorylase/Platelet derived endothelial cell growth factor. Results: The levels of markers of oxidative stress along with the activity of thymidine phosphorylase were found to be significantly higher in the study subjects in comparison to healthy controls. The results indicate oxidative stress and angiogenesis activity increase progressively with the increase in staging and progression of disease. Conclusion: Oxidative stress and expression of angiogenesis activity points clearly that with the progression of oxidative stress there is a simultaneous progression of angiogenesis in relation to disease progression, clinical stage and cytological grade in the pathophysiology of prostate carcinoma.